Dual‐earner parent couples’ work and care during COVID‐19 - Craig, Lyn (Gend Work Organ, 2020)
COVID‐19 and the associated lockdowns meant many working parents were faced with doing paid work and family care at home simultaneously. To investigate how they managed, this article draws a subsample of parents in dual‐earner couples (n = 1536) from a national survey of 2722 Australian men and women conducted during lockdown in May 2020. It asked how much time respondents spent in paid and unpaid labour, including both active and supervisory care, and about their satisfaction with work–family balance and how their partner shared the load. Overall, paid work time was slightly lower and unpaid work time was very much higher during lockdown than before it. These time changes were most for mothers, but gender gaps somewhat narrowed because the relative increase in childcare was higher for fathers. More mothers than fathers were dissatisfied with their work–family balance and partner’s share before COVID‐19. For some the pandemic improved satisfaction levels, but for most they became worse. Again, some gender differences narrowed, mainly because more fathers also felt negatively during lockdown than they had before.